Periodic normalization of the translaminar pressure gradient prevents glaucomatous damage. (November 2020) - Berdahl, John P.; Ferguson, Tanner J.; Samuelson, Thomas W.
Abstract: The 24-hour intraocular pressure (IOP) rhythm is of interest to clinicians but its overall impact on glaucomatous progression remains unclear. Recent evidence has implicated the translaminar pressure gradient (TLPG), or imbalance between IOP and intracranial pressure, in the development of glaucoma. Evidence suggests that retinal ganglion cell death occurs as a result of decreased axonal transport only after a sustained, elevated TLPG. We hypothesize that periodic normalization of the TLPG prevents glaucomatous damage by enabling temporary resumption of axonal transport. Temporary resumption of axonal transport allows for delivery of critical metabolic cargoes with concomitant removal of metabolic waste which prevents apoptosis of the retinal ganglion cell.